(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Study of the social, political, and economic environment is the focus of the multidisciplinary,area called as cultural studies. It mostly uses an interdisciplinary approach to study global studies. This global agenda includes the problems of the people with regards to race, class, caste, gender, and even nation. The current study focusis placed throughout the study on the notion that Frances Ellen Watkins Harper was a key voice for the voiceless, as expressed in her writings. The voice that Frances Harper developed both during and after the Civil War continues to be vital to comprehending the nation and finding solutions for its problems. This essay attempts to illustrate Frances Harper’s relationship to society and its significance for the nation’s growth, with cultural research serving as one of the key components of comprehending society. The author of Learning to Read describes the state of Black people and their never-ending efforts for education and social rights.